Towards a Psychology of Rural Development Processes and Interventions. (7th February 2014) - Landini, Fernando; Leeuwis, Cees; Long, Norman; Murtagh, Sofía
ABSTRACT A psychosocial approach to rural development and development interventions, which we designate as 'psychology of rural development' (PsyRD), does not yet exist as an area of research or intervention within the field of psychology or development studies, even though rural development is in part obviously shaped by psychosocial factors. Thus, in this discussion paper, we argue the need for PsyRD, explore how it may provide new insights and tools for analysis vis‐à‐vis rural development scenarios and issues of social equity and outline the shape that, in our view, such a psychology should take. First, the multiple dimensions of rural development and the many practical problems faced by rural development agents contain strong psychosocial elements that require contributions from psychology. Yet at the same time, the psychological literature on this topic contains many limitations and biases, which leads us to, in the second part of the paper lay the groundwork for a PsyRD that focuses on the importance of adopting a critical and interdisciplinary approach capable of dealing with complexity and multidetermination. Finally, we conclude by outlining the challenges of PsyRD. Copyright © 2014 John Wiley & Sons, Ltd.